Propriedades de medida de resultados relatados pelo paciente que avaliam a autoimagem genital: uma revisão sistemática - Silva, Erisvan Vieira da (2024)
Genital self-image (GSI) includes feelings, attitudes, thoughts, and behaviors related to one's genitals. Patient-Reported Outcome Measures (PROMs) are commonly used to assess GSI and focus on patient self-report. Several PROMs are available, but their measurement properties vary between instruments and populations. Therefore, this systematic review aimed to identify and evaluate the measurement properties, feasibility, and interpretability of PROMs assessing GSI in women and men ≥ 16 years of age to support evidence-based recommendations for selecting the most appropriate PROM. It was conducted according to the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) in eight steps, including: literature search, assessment of measurement properties, and recommendation of PROM(s). First, a search of PubMed and PROSPERO was performed to identify previous reviews or registries. The search strategy was developed using keywords and MeSH terms from the literature and consultations with experts. The following descriptors and their English acronyms were combined for each database: "genital self-image", "genital image", "genital", "genital perception", "genital appearance", and "genital self image". The search filter developed by the COSMIN initiative for measurement properties of measurement instruments was added to the search. The Medline, Embase, Web of Science, SciELO and CINAHL databases were searched for studies evaluating the measurement properties of PROMs for GSI published up to November 2023. The COSMIN risk of bias checklist was used, applying the quality criteria for good measurement properties, and the evidence was summarized and its quality assessed using the modified GRADE approach. Therefore, to determine the overall quality of a PROM, the consistency of the results of the available studies was assessed for each measurement property. Consistent results were summarized and compared with established criteria to classify the measurement characteristic as sufficient, insufficient, inconsistent, or indeterminate. The quality of evidence was then categorized as high, moderate, low, or very low. Twenty-two studies and 9 PROMs were analyzed, but no definitive conclusions could be drawn about the PROMs evaluated. For the assessment of female GA, the 7-item version of the Female Genital Self-Image Scale (FGSIS-7) showed potential to be recommended. However, no PROM for the male population showed at least low-quality evidence for content validity and no recommendation was made. Future studies should collect additional data to assess measurement properties according to a robust, guideline-based methodology for conducting measurement properties studies of PROMs. It is also recommended that PROMs be developed according to the COSMIN methodology.